Minat Belajar Musik Instant Akibat Respon Berulang Dan Menyenangkan Pada Ajang Pentas Kompetisi Musik Populer; “Studi Kasus Pendidikan Musik Nonformal dalam Sudut Pandang Teori Belajar Operant Conditioning BF. Skinner” - Esy Maestro; Mudjiran Mudjiran (SENDRATASIK UNP, 2021)
Thedevelopment of music in modern and urban society today is not always driven by the awareness of the importance of formal education in the field of music itself. The behavior of the community that develops in the surrounding environment, psychologically has triggered   the interest of some individuals to engage in the phenomenon of populist music culture, one of which is budaya K-pop who participated in fertilizing music talent search competitions such astelevision, initiated bylocalgovernments, and certain nongovernmental organizations. Many parents consider that their children need to take part  either  as serious participants or just perform in the  event. Many young people and their parents are willingto spendmoney, time, energy, and   cost in order to be exposed to the event that is considered prestigious. The continuation is predictable, while the prizes are obtained,of coursepopularity  follows, because they will be widely published by the services of the media and television. A number  of thesefinancial r ewards  and popularity  will be  enjoyable. The behavior to repeat  and  keep repeating the participation  ofchildren in this event , aslong asitcauses them to havebeen trapped in the behavior of operant conditioning. So BF. Skinner has explained that if a stimulus produces a pleasant reward support  capacity,there  will be consequences for repeated behavioral  responses.   Because it will repeat itself, some young people are trying to develop their musical interests by learning music from an early age or studying it in formal education. But the irony for some of them is that it synergizes with the impatience of their parents, to learn music in more results-oriented and   instantaneous music courses. The  managers of this kind of non-formal music education institutions seem to also care about the quality of music education, unless they also feel equally profiting momentarily from this phenomenon. Eventually many participants of the  courseand tutors   were disappointed at the incompatibility of the results obtained with all the power that had been sacrificed. In fact, it is still the really talented children who continue to advance to win this talent search competition, even though there are actually some of these champions who learn or do not need to study in courses and less private  music.